The Works of Aleksandar Petrov and the reception of his opus, with a special reference about Poland - Ratković, Dragana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
In this paper, we present and analyze the creativity of Aleksandar Petrov, and the reception of his work in the country and abroad. In the first part, Petrov’s literary and scientific work and its reception in Serbia and the world are described, and in the second—we give Petrov’s view on poetry and prose, and we write about its reception in Poland. The subject of the analysis in the second part consists of the following: the poetry published in the January issue of the magazine Creativity (Twórczość) in 1987, the collection of peoms Gold in fire (Złoto w ogniu) from 2005, Alexandria with Ithaca in mind (Aleksandria z Itaką w pamięci) from 2013, and an excerpt from Turkish Vienna (2000) called „October again” (Znów październik), published in the no. 1-3 of the magazine Tygiel kultury of Łódź in 2007.